The Impact of Workload During the Productive Age on Hypertension in Elderly Patients at Lisna YPK PLN Clinic Lampung - Ajirnii Qalibun; Nurul Aziza; Nur Sefa Arief Hermawan (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction : Hypertension is often compared to a silent ticking clock in the body, striking unexpectedly with cardiovascular disease. Among its many triggers, occupational workload during productive years is often overlooked, though it may leave scars that surface as hypertension in later life. Objectives : This study assessed the association between past workload and hypertension among elderly patients at Klinik Lisna YPK PLN Lampung. Methods : A cross-sectional quantitative study was carried out in June 2025. From 215 elderly patients, 140 were purposively selected. Workload history was measured using the NASA-TLX questionnaire, while hypertension status was obtained from medical records and blood pressure checks. The dataset was examined through Mann–Whitney U testing and logistic regression, adopting a significance level of 0.05. Results : Most respondents reported high workload (62.86%), followed by very high (24.29%) and moderately high (12.86%). Hypertension was found in 50% of participants. A significant association was observed (p = 0.000274). Logistic regression showed that high workload increased hypertension risk 4.128 times (p = 0.020), and very high workload 4.118 times (p = 0.031), compared to moderate workload. Conclusion : Workload in productive years is like a shadow that follows into old age, shaping the risk of hypertension. Incorporating occupational history into screening may open the door to earlier detection and better prevention for the elderly.